2023
DOI: 10.1097/mbp.0000000000000660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blood pressure measurements on the bare and sleeved arms – what does it uncover?

Abstract: Accurate office blood pressure (BP) measurement remains crucial in diagnosing and managing hypertension. In this study, we aimed to compare BP measurements done over a bare arm versus a sleeved arm, while controlling all other possible sources of variance. We collected BP measurements of 100 hypertensive patients visiting a nephrology and hypertension clinic between January 2019 and December 2023. Measurements were taken by a single operator and according to the updated guidelines. BP measurements were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recently, Tal-Ben et al [19] reported differences between sleeved and bare arms measurements based on "absolute values" and recommend measuring blood pressure on bare skin because the effect seems to be "unpredictable"; however, the same study did not find statistical significant differences between the sleeved and the bare arm measurements, despite the collected blood pressure were done simultaneously in the right and left arm, where we presume differences.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, Tal-Ben et al [19] reported differences between sleeved and bare arms measurements based on "absolute values" and recommend measuring blood pressure on bare skin because the effect seems to be "unpredictable"; however, the same study did not find statistical significant differences between the sleeved and the bare arm measurements, despite the collected blood pressure were done simultaneously in the right and left arm, where we presume differences.…”
Section: Discussionmentioning
confidence: 72%